The TRANZAC and Social Problems re: COVID 19 and Performing Musicians - Wiseman, Bob (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Exploring COVID-19 through the TRANZAC, a Toronto performance hub. This piece is in the form of a zine.